Long-term quality of life after surgery of head and neck cancer with microvascular reconstruction: a prospective study with 4.9-years follow-up - Kainulainen S; Koivusalo AM; Roine RP; Wilkman T; Sintonen H; Törnwall J; Thorén H; Lassus P (SPRINGER HEIDELBERG, 2025)
Purpose
The aim of this study was to evaluate the long-term health-related quality of life (HRQoL) of head and neck cancer patients with microvascular surgery. Surgical treatment causes great changes in patient HRQoL. Studies focusing on long-term HRQoL after microvascular reconstruction for head and neck cancer patients are scarce.
Methods
We conducted a prospective study of 93 patients with head and neck cancer and microvascular reconstruction in Helsinki University Hospital Finland. HRQoL was measured using the 15D instrument at baseline and after a mean 4.9-years follow up. Results were compared with those of an age-standardized general population.
Results
Of the 93 patients, 61 (66%) were alive after follow-up; of these, 42 (69%) answered the follow-up questionnaire. The median time between surgery and HRQoL assessment was 4.9 years (range 3.7–7.8 years). The mean 15D score of all patients (n = 42) at the 4.9-years follow up was statistically significantly (p = 0.010) and clinically importantly lower than at baseline. The dimensions of “speech” and “usual activities” were significantly impaired at the end of follow up. There was a significant difference at the 4.9-years follow-up in the mean 15D score between patients and the general population (p = 0.014). After follow up, patients were significantly (p < 0.05) worse off on the dimensions of “speech,” “eating,” and “usual activities.”
Conclusions
Long-term HRQoL was significantly reduced in the whole patient cohort. Speech and usual activities were the most affected dimensions in head and neck cancer patients with microvascular reconstruction at the end of the 4.9-years follow up.